Verrucous hemangioma treated with electrocautory - Achar Arun; Biswas Surajit; Maity Ashoke; Naskar Biswanath (Wolters Kluwer Medknow Publications, 2009)
Verrucous hemangioma is a rare form of vascular malformation which is usually congenital. Most of the cases present as wart-like dark blue to erythematous papules, nodules and plaques with special predilection in lower extrimities. We are reporting here a 19-year-old Muslim patient with large Verrucous hemangioma in the left leg along with discending of right shoulder without any signs of neurological involvement. Patient was successfully treated with repeat serial Electrocautory.